2019
DOI: 10.1042/bcj20190633
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of human placental aromataseCYP19A1

Abstract: Aromatase CYP19A1 catalyzes the synthesis of estrogens in endocrine, reproductive and central nervous systems. Higher levels of 17β-estradiol (E2) are associated with malignancies and diseases of the breast, ovary and endometrium, while low E2 levels increase the risk for osteoporosis, cardiovascular diseases and cognitive disorders. E2, the transcriptional activator of the estrogen receptors, is also known to be involved in non-genomic signaling as a neurotransmitter/neuromodulator, with recent evidence for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…A final wash with 50% CH 3 CN/10 mM NH 4 HCO 3 was given and gel pieces were completely dried prior to removal of the wash solution. Trypsin digestion was carried out by incubating the sample at 37°C for 18 h and the samples were stored at -20°C until analysis ( Ghosh et al., 2019 ). The trypsin digested proteins products were fractionated using LC-MS/MS.…”
Section: Methodsmentioning
confidence: 99%
“…A final wash with 50% CH 3 CN/10 mM NH 4 HCO 3 was given and gel pieces were completely dried prior to removal of the wash solution. Trypsin digestion was carried out by incubating the sample at 37°C for 18 h and the samples were stored at -20°C until analysis ( Ghosh et al., 2019 ). The trypsin digested proteins products were fractionated using LC-MS/MS.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical and bioinformatics results highlighted the important roles of rs28757157, rs3751592, and rs59429575 in the outset of lung cancer in the total or stratified population, which helped improve our understanding of CYP19A1 in this disease. CYP19A1 gene, encoding aromatase and responsible for the final step in the biosynthesis of estrogens, estradiol (E2) and estrone (E1), has been intensively investigated [25,26]. It has been identified that SNPs in the intron region of CYP19A1 play an important role in the transcriptional regulation and splicing of CYP19A1 and could produce some different enzymes with diverse enzyme activity compared with normal gene products [27].…”
Section: Discussionmentioning
confidence: 99%
“…The increased PGE2 production in L/H-Pgds -/-uteri might be linked to the up-regulation of StAR that encodes the rate-limiting factor in steroid biosynthesis; however, Scc and Cyp19a1 transcriptional levels were not changed. CYP19a1 upregulation in L/H-Pgds -/-uteri, without any transcriptional modification of the gene expression via PGE2 (Attar et al, 2009), suggests that PGD2 might be involved in CYP19a1 post-transcriptional/translational regulation or in the regulation of its stability (Ghosh et al, 2019, Molehin et al, 2018. Together with CYP19a1 upregulation, the modified expression of HSD17B2 and HSD17B7, two E2 metabolic enzymes, suggests that the local oestrogen metabolism is modified in the absence of PGD2, as reported in human endometriosis (Attar et al, 2009, Delvoux et al, 2009, Huhtinen et al, 2012b and adenomyosis (Kitawaki, 2006, Maia et al, 2006, Takahashi et al, 1989.…”
Section: Discussionmentioning
confidence: 99%
“…Additional experiments (i.e. high-throughput transcriptomic analysis, in vitro analysis) are needed to evaluate the direct or indirect mechanisms initiated by PGD2 and involved in the post-transcriptional/translational regulation of ESR1-2, COX1, COX2, CYP19a1(Otto et al, 1993, Wada et al, 2009, Yu and Kim, 2012, Jaen et al, 2018, Molehin et al, 2018, Ghosh et al, 2019, thus affecting their expression, stability and/or their subcellular localisation.…”
mentioning
confidence: 99%